Intellectual property, public health and access to medicines in international organizations - Germán Velásquez (South Centre, 2017)
This South Centre research paper by Dr. German Velasquez describes and analyses the mandate, programmes, strategies, and activities that different international organizations such as WHO, WTO, WIPO, UNCTAD, UNDP, UNAIDS, the UN Human Rights Council, and the UN Secretary-General's High Level Panel (UNHLP) on access to medicines have undertaken on the subject of access to medicines, intellectual property, international trade rules and human rights. The paper also analyses two cases of existing inter-agency cooperation: the WHO-WTO-WIPO tripartite partnership and the WHO, UNDP and UNCTAD collaboration for developing guidelines for the examination of pharmaceutical patents from a public health perspective.
Keywords: 300; Arzneimittel; Arzneimittelrecht; Immaterialgüterrechte; Gesundheitsversorgung; Internationale Organisation; Welt